Pogled (ustavnega) sodnika - Zobec, Jan (Podjetje in delo, 2014)
Constitutionality, as a modern legal culture, fundamentally revises traditional approaches to the relationship between law and morality. The concept of capillary constitutionalisation together with the whole set of tools, designed to assure its practical efficiency, leads to a general feeling that anomalies and abuses of law which were taking place in the totalitarian regimes of the last century could not revisit any more. However, the reality demonstrates that the legal framework is just the formal condition for the moral-ethical efficiency of law. In the end, everything depends on personal characteristics and integrity of those who are entrusted with the practical enforcement of the constitutionality.
Keywords: law; morala; morality; pravna načela; pravo; ustavnost